Stand aside stomata, another actor deserves centre stage the forgotten role of the internal conductance to CO2 transfer - Warren, Charles R (Journal of experimental botany, 2008)
Internal conductance describes the movement of CO(2) from substomatal cavities to sites of carboxylation. Internal conductance has now been measured in approximately 50 species, and in all of these species it is a large limitation of photosynthesis. It accounts for somewhat less than half of the decrease in CO(2) concentrations from the atmosphere to sites of carboxylation. There have been two major findings in the past decade. First, the limitation due to internal conductance (i.e. C(i)-C(c)) is not fixed but varies among species and functional groups. Second, internal conductance is affected by some environmental variables and can change rapidly, for example, in response to leaf temperature, drought stress or CO(2) concentration. Biochemical factors such as carbonic anhydrase or aquaporins are probably responsible for these rapid changes. The determinants of internal conductance remain elusive, but are probably a combination of leaf anatomy, morphology, and biochemical factors. In most plants, the gas phase component of internal conductance is negligible with the majority of resistance resting in the liquid phase from cell walls to sites of carboxylation. The internal conductance story is far from complete and many exciting challenges remain. Internal conductance ought to be included in models of canopy photosynthesis, but before this is feasible additional data on the variation in internal conductance among and within species are urgently required. Future research should also focus on teasing apart the different steps in the diffusion pathway (intercellular spaces, cell wall, plasmalemma, cytosol, and chloroplast envelope) since it is likely that this will provide clues as to what determines internal conductance